Quantification of cellular and nuclear uptake rates of polymeric gene delivery nanoparticles and DNA plasmids via flow cytometry. (June 2016) - Bishop, Corey J.; Majewski, Rebecca L.; Guiriba, Toni-Rose M.; Wilson, David R.; Bhise, Nupura S.; Quiñones-Hinojosa, Alfredo; Green, Jordan J.
Graphical abstract: Abstract: Non-viral, biomaterial-mediated gene delivery has the potential to treat many diseases, but is limited by low efficacy. Elucidating the bottlenecks of plasmid mass transfer can enable an improved understanding of biomaterial structure–function relationships, leading to next-generation rationally designed non-viral gene delivery vectors. As proof of principle, we transfected human primary glioblastoma cells using a poly(beta-amino ester) complexed with eGFP plasmid DNA. The polyplexes transfected 70.6 ± 0.6% of the cells with 101 ± 3% viability. The amount of DNA within the cytoplasm, nuclear envelope, and nuclei was assessed at multiple time points using fluorescent dye conjugated plasmid up to 24 h post-transfection using a quantitative multi-well plate-based flow cytometry assay. Conversion to plasmid counts and degradation kinetics were accounted for via quantitative PCR (plasmid degradation rate constants were determined to be 0.62 h −1 and 0.084 h −1 for fast and slow phases respectively). Quantitative cellular uptake, nuclear association, and nuclear uptake rate constants were determined by using a four-compartment first order mass-action model. The rate limiting step for these poly(beta-amino ester)/DNA polyplex nanoparticles was determined to be cellular uptake (7.5 × 10 −4 h −1 ) and only 0.1% of the added dose was taken up by the human brain cancer cells, whereas 12% of internalized DNA successfully entered the nucleus (the rate of nuclear internalization of nuclear associated plasmid was 1.1 h −1 ). We describe an efficient new method for assessing cellular and nuclear uptake rates of non-viral gene delivery nanoparticles using flow cytometry to improve understanding and design of polymeric gene delivery nanoparticles. Statement of Significance: In this work, a quantitative high throughput flow cytometry-based assay and computational modeling approach was developed for assessing cellular and nuclear uptake rates of non-viral gene delivery nanoparticles. This method is significant as it can be used to elucidate structure–function relationships of gene delivery nanoparticles and improve their efficiency. This method was applied to a particular type of biodegradable polymer, a poly(beta-amino ester), that transfected human brain cancer cells with high efficacy and without cytotoxicity. A four-compartment first order mass-action kinetics model was found to model the experimental transport data well without requiring external fitting parameters. Quantitative rate constants were identified for the intracellular transport, including DNA degradation rate from polyplexes, cellular uptake rate, and nuclear uptake rate, with cellular uptake identified as the rate-limiting step.